Ecophysiological and phytochemical response to ozone of wine grape cultivars of Vitis vinifera L. Issue 22 (16th November 2016) - Valletta, Alessio; Salvatori, Elisabetta; Rita Santamaria, Anna; Nicoletti, Marcello; Toniolo, Chiara; Caboni, Emilia; Bernardini, Alessandra; Pasqua, Gabriella; Manes, Fausto
Abstract: Vitis vinifera sensitivity to tropospheric ozone (O3 ) has been evidenced in several studies. In this work, physiological and metabolic effects of O3 on two wine cultivars of V. vinifera (i.e. Maturano and San Giuseppe) have been studied. Moreover, chlorogenic acid (CGA) production, in consideration of its importance in the biosynthetic pathway of polyphenols and as antioxidant, has been investigated. Maturano cultivar resulted more sensitive to O3, as evidenced by the gas exchange reduction at the early stage of treatment, and by the increase in Ci/Ca and the decoupling of net photosynthesis and the stomatal conductance at the end of the treatment. Unexpectedly, O3 did not activate stilbene production. Ozone induced an early CGA decrease, significantly more consistent in cv. Maturano, and an increase after 8 days, more consistent in cv. S. Giuseppe. These results suggest that CGA could be considered a biochemical marker of O3 -induced stress in V. vinifera . Abstract :